THE PROCEDURE FOR ENTERING CITIZENS INTO PUBLIC SERVICE (World Bulletin of Management and Law, 2025)
It is considered one of the most important institutions that organize the activities of the public service, state bodies and organizations. The development and effective functioning of each state is directly related to the involvement of its citizens in public service. Therefore, it is necessary that the procedure and criteria for the admission of citizens to public service are clearly established. The correct and fair functioning of these procedures ensures the social justice of the state, the protection of the rights and freedoms of citizens. In this article, information about the procedure for entering citizens into public service is collected and the topic is discussed in detail.